OBJECT TRACKING VIA COMPARISON OF COLOR HISTOGRAMS - B. A. Zalesky; E. N. Seredin; M. V. Yadlouski (Informatika)
Three versions of a histogram algorithm for tracking objects on video sequences made by an unstable camera are presented. Local color 1D-histograms of pixels and local color 2D-histograms of pairs of adjacent pixels are used in all versions as region features. The histograms are compared by the Bhattacharia criterion. А parallel computing platform CUDA, developed to program GPUs, allows creation of real time or near-real time program realizations of the offered versions. Results of comparison of the versions with the known mean shift algorithm and correlation type algorithms are also presented. It is shown by experiments that the versions are more accurate and reliable than the mean shift algorithm, which estimates similarity of linear approximations of local histograms, and more robust with respect to the video quality than the correlation algorithms.